The role of seasonal flowering responses in adaptation of grasses to temperate climates - Fjellheim, Siri; Boden, Scott; Trevaskis, Ben (Frontiers in Plant Science, 2014)
Grasses of the subfamily Pooideae, which includes important cereal crops and pasture grasses, are widespread in temperate zones. Seasonal regulation of developmental transitions coordinates the life cycles of Pooideae with the passing seasons, so that flowering and seed production coincide with favourable conditions in spring. This review examines the molecular pathways that control the seasonal flowering responses of Pooideae and how variation in the activity of genes controlling these pathways can adapt cereals or grasses to different climates and geographical regions. The possible evolutionary origins of the seasonal flowering responses of the Pooideae are discussed and key questions for future research highlighted. These include the need to develop a better understanding of the molecular basis for seasonal flowering in perennial Pooideae and in temperate grasses outside the core Pooideae group.